SOURCES OF FINANCING TASKS FOR PUBLIC HIGHER EDUCATION INSTITUTIONS: FINDINGS IN LIGHT OF THEIR REPORTING - Aleksandra Pisarska (Polityki Europejskie, Finanse i Marketing)
The purpose of this study is to recognize the share of self-generated sources of financing for activities of public higher education institutions as part of their general stream of financing. Therefore, the key question that will be answered in this study is: how is the structure of financing sources of a studied institution of higher education formed? In the theoretical section, findings were based on the results of literature research. In turn, in the empirical part, findings were based on the results of a case study supported by observation in a multi-field participating university. The entity's financial statements were also used. On the basis of the research results, the structure of financing sources for the studied public institution of higher education was determined, indicating the possibility of using the entity's financial reporting for this purpose. It was noticed, based on the classification of the sources of financial supply indicated in the literature, that they are heterogeneous – drawn from both the public and private sectors. An increase in the share of funds supplied from the private sector was also revealed. In turn, private sources mainly came from fees related to the teaching process. Private sources also included those from commercialization of research results. The research presented in the study has provided new knowledge about the structure of the financing sources of a public education of higher institution in the context of current conditions for its functioning. In particular, the research helps supplement the existing scarcity of knowledge about the share of self-generated financing for a public higher education institution in the general financing stream of its activities.